2007
DOI: 10.1149/1.2779962
|View full text |Cite
|
Sign up to set email alerts
|

Li Ion Conducting Polymer Gel Electrolytes Based on Ionic Liquid/PVDF-HFP Blends

Abstract: Ionic liquids thermodynamically compatible with Li metal are very promising for applications to rechargeable lithium batteries. 1-methyl-3-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide (P 13 TFSI) is screened out as a particularly promising ionic liquid in this study. Dimensionally stable, elastic, flexible, nonvolatile polymer gel electrolytes (PGEs) with high electrochemical stabilities, high ionic conductivities and other desirable properties have been synthesized by dissolving Li imide salt (LiTFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(144 citation statements)
references
References 37 publications
(103 reference statements)
2
141
0
1
Order By: Relevance
“…[270] Similarly,Y ee tal., [271] Navarra et al, [272] and Hofmann et al [273] reported very promising resultsi nt erms of safety and electrochemical performance for PVdF-HFP-based quaternary electrolyte systems; this also revealed good compatibility with graphite anodes and Li(Ni 1/3 Mn 1/3 Co 1/3 )O 2 cathodes. Nevertheless, intrinsic safety issues related to the utilization of volatile and flammable organic solvents might be substantially reduced, but not completely overcome.…”
Section: Alkyl Carbonate/il/solid Polymer Blends (Ole-il-spes)mentioning
confidence: 93%
“…[270] Similarly,Y ee tal., [271] Navarra et al, [272] and Hofmann et al [273] reported very promising resultsi nt erms of safety and electrochemical performance for PVdF-HFP-based quaternary electrolyte systems; this also revealed good compatibility with graphite anodes and Li(Ni 1/3 Mn 1/3 Co 1/3 )O 2 cathodes. Nevertheless, intrinsic safety issues related to the utilization of volatile and flammable organic solvents might be substantially reduced, but not completely overcome.…”
Section: Alkyl Carbonate/il/solid Polymer Blends (Ole-il-spes)mentioning
confidence: 93%
“…They also reported that surface tension and viscoelastic properties were the main parameters for bead generation. The net charge density carried by the electrospinning jet, solution viscosity, and surface tension of the polymer solutions are the main factors that influence bead formations [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the good thermal, electrochemical, and interfacial properties of this type of hybrid membranes have been demonstrated in our laboratory [19] and in other laboratories. [20,21] Therefore, it appeared to us of interest to extend the study by considering a new organic solvent mixture (EC-PC-DMC) and evaluating its effect on the performances of PVdF-HFP membranes containing LiTFSI-Py 24 TFSI electrolyte solutions. We expected that the use of the ternary organic solvent mixture would lead to important advances in terms of: a) enhancement of ion dissociation owing to the high dielectric constants of both EC and PC; b) optimization of interfacial behavior owing to the passivating film-forming ability of EC; [22] c) improvement of fast ion transport owing to the low viscosity of DMC and d) widening of the temperature range of high ionic conductivity owing to the synergic effect of the three solvents with the thermally stable ionic liquid component.…”
Section: Resultsmentioning
confidence: 99%